Occupational health hazards on workers exposure to lead (Pb): A genotoxicity analysis - Balamuralikrishnan Balasubramanian; Arun Meyyazhagan; Ashok Jeyaram Chinnappan; Karthick Kumar Alagamuthu; Sureshkumar Shanmugam; Naif Abdullah Al-Dhabi; Abdul Kareem Mohammed Ghilan; Veeramuthu Duraipandiyan; Mariadhas Valan Arasu (Elsevier, 2020)
Background: The present investigation of genotoxicity of lead (Pb) among workers exposed to inorganic Pb environment, which appears to be first of its kind in South India, was undertaken to assess the seriousness, the ill effects of health contributed by this serious environmental pollutant. Methods: A total of 144 samples comprising of exposed (n = 72), and control (n = 72) subjects were screened. Demographic data and their associated health levels were undertaken by means of a questionnaire. The blood samples collected were subjected to chromosomal analysis, micronuclei assessment and comet assay. Results: A higher level of Pb was quantified in the blood samples of all exposed subjects. An overview of the genotoxic assessment helped us understand parameters such as age do not affect or bring about any difference in the genotoxic potential of the exposed and control subjects. The only signification feature that resulted in an enhanced genotoxic potential was the years of exposure to the Pb environment that accumulated the dosage of Pb over the years. Conclusion: The high positivity of genotoxic potential of Pb in a country like India highlights the need for labelling hazardous metals in paint containers as a means to assure strict regulations. Keywords: Chemical exposure, Chromosomal alteration, Comet assay, Genotoxicity, Micronuclei assay